Integrated Uniformly Microporous C4N/Multi‐Walled Carbon Nanotubes Composite Toward Ultra‐Stable and Ultralow‐Temperature Proton Batteries. Issue 16 (24th January 2023) - Yang, Mingsheng; Zhao, Qian; Ma, Huige; Li, Rui; Wang, Yan; Zhou, Rongkun; Liu, Jieyuan; Wang, Xinyu; Hao, Yuxin; Ren, Jiayi; Zheng, Zilong; Zhang, Naibo; et al.
Abstract: Benefiting from the proton's small size and ultrahigh mobility in water, aqueous proton batteries are regarded as an attractive candidate for high‐power and ultralow‐temperature energy storage devices. Herein, a new‐type C4 N polymer with uniform micropores and a large specific surface area is prepared by sulfuric acid‐catalyzed ketone amine condensation reaction and employed as the electrode of proton batteries. Multi‐walled carbon nanotubes (MWCNT) are introduced to induce the in situ growth of C4 N, and reaped significantly enhanced porosity and conductivity, and thus better both room‐ and low‐temperature performance. When coupled with MnO2 @Carbon fiber (MnO2 @CF) cathode, MnO2 @CF//C4 N‐50% MWCNT full battery shows unprecedented cycle stability with a capacity retention of 98% after 11 000 cycles at 10 A g −1 and even 100% after 70 000 cycles at 20 A g −1 . Additionally, a novel anti‐freezing electrolyte (5 m H2 SO4  + 0.5 m MnSO4 ) is developed and showed a high ionic conductivity of 123.2 mS cm −1 at ‐70 °C. The resultant MnO2 @CF//C4 N‐50% MWCNT battery delivers a specific capacity of 110.5 mAh g −1 even at ‐70 °C at 1 A g −1, the highest in all reported proton batteries under the same conditions. This work is expected to offer a package solution for constructing high‐performance ultralow‐temperature aqueous proton batteries. Abstract : MnO2 @CF//C4 N‐50% multi‐walled carbon nanotubes full battery delivers a capacity retention of 98% after 11 000 cycles at 10 A g −1 and 100% after 70 000 cycles at 20 A g −1 at 25 °C. Even at −70 °C, the full battery still exhibits a discharge capacity of 110.5 mAh g −1 at 1 A g −1 .